2016
DOI: 10.3945/jn.115.220152
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Isomers of Sialyllactose Increase Ganglioside Sialic Acid Concentrations in the Corpus Callosum and Cerebellum and Modulate the Colonic Microbiota of Formula-Fed Piglets

Abstract: Supplementation of formula with 3'- or 6'-sialyllactose can enrich ganglioside SA in the brain and modulate gut-associated microbiota in neonatal pigs. We propose 2 potential routes by which sialyllactose may positively affect the neonate: serving as a source of SA for neurologic development and promoting beneficial microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 65 publications
7
105
2
1
Order By: Relevance
“…Oligosaccharides are increasingly recognized as bioactive components of milk, and are believed to have an impact on the early development of the neonate [22]. Sialic acid-containing oligosaccharides have been implicated in inhibition of pathogen adhesion to host cells, immune system maturation, brain development, and modulation of the gut microbiota [23][24][25]. For example, 6 -SL was shown to reduce rotavirus (RV) infectivity in vitro at concentration levels of 2 to 6 mg/mL [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oligosaccharides are increasingly recognized as bioactive components of milk, and are believed to have an impact on the early development of the neonate [22]. Sialic acid-containing oligosaccharides have been implicated in inhibition of pathogen adhesion to host cells, immune system maturation, brain development, and modulation of the gut microbiota [23][24][25]. For example, 6 -SL was shown to reduce rotavirus (RV) infectivity in vitro at concentration levels of 2 to 6 mg/mL [26].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of cognitive development, 6 -SL is an integral component of gangliosides and signaling molecules in the brain, and studies have suggested an association between sialic acid-bound gangliosides and glycoproteins with improved learning ability [28,29]. Jacobi et al [23] reported that formula supplementation with 2 g/L 6 -SL significantly increased the ganglioside-bound SA content in the corpus callosum of pigs compared to piglets receiving non-supplemented formula. Furthermore, Jacobi et al [23] demonstrated a prebiotic action of 6 -SL to modulate the gut microbiome [23].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, SA supplementation in piglets has been shown to influence gene expression for neural cell adhesion molecules (16) and enhance learning and memory (7). Supplementation of sialyllactose increased ganglioside bound SA in the corpus callosum of piglets (17). Provided the multitude of ways in which SA supplementation influences infant development, there is interest in characterizing changes in free and bound SA in expressed milk throughout lactation.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding rat pups and piglets with a diet rich in SA is reported to upregulate expression of the learning genes Gne and ST8SiaIV, and to promote cognitive functioning, which should be confirmed in further experiments. Also, whether SA or sialyl‐lactose is incorporated into brain gangliosides as reported needs to be confirmed in further studies …”
Section: Functions Of Hmosmentioning
confidence: 93%